Dog skin parasite load, TLR-2, IL-10 and TNF-α expression and infectiousness - Pereira-Fonseca, D. C.M. [UNESP]; Oliveira-Rovai, F. M. [UNESP]; Rodas, L. A.C. [UNESP]; Beloti, C. A.C. [UNESP]; Torrecilha, R. B.P. [UNESP]; Ito, P. K.R.K. [UNESP]; Avanço, S. V.; Cipriano, R. S.; Utsunomiya, Y. T. [UNESP]; Hiramoto, R. M.; Calvo-Bado, L.; Courtenay, O.; et al. (Wiley, 2017)
Visceral leishmaniosis is a zoonotic disease that is transmitted by Lutzomyia longipalpis sandflies. Dogs are the main peri-urban reservoir of the disease, and progression of canine leishmaniosis is dependent on the type of immune response elaborated against the parasite. Type 1 immunity is characterized by effective cellular response, with production of pro-inflammatory cytokines such as tumour necrosis factor alpha (TNF-α). In contrast, Type 2 immunity is predominantly humoral, associated with progression of the disease and mediated by anti-inflammatory cytokines such as interleukin 10 (IL-10). Although seemly important in the dynamics of leishmaniosis, other gene products such as toll-like receptor 2 (TRL-2) and inducible nitric oxide synthase (iNOS) exert unclear roles in the determination of the type of immune response. Given that the dog skin serves as a micro-environment for the multiplication of Leishmania spp., we investigated the parasite load and the expression of TLR-2, iNOS, IL-10 and TNF-α in the skin of 29 infected and 8 control dogs. We found that increased parasite load leads to upregulation of TLR-2, IL-10 and TNF-α, indicating that abundance of these transcripts is associated with infection. We also performed a xenodiagnosis to demonstrate that increased parasitism is a risk factor for infectiousness to sandflies.
Keywords: canine; cytokine; disease; gene expression; Leishmania spp; Leishmaniasis; parasite